P196 The national census of UK endoscopy services 2021. (19th June 2022) - Ravindran, Srivathsan; Marshall, Sarah; Healey, Chris; Ashrafian, Hutan; Darzi, Ara; Coleman, Mark; Thomas-Gibson, Siwan
Abstract : Introduction: The Joint Advisory Group (JAG) on Gastrointestinal (GI) Endoscopy biennial census provides an insight into the provision of UK endoscopy services. We report on the 2021 census which was conducted to understand the impact of COVID-19 and ongoing pressures on endoscopy services. Methods: The census was disseminated to all JAG-registered services in April 2021 using an online survey platform. Prior to analysis, any missing data from services was sought as part of a second step verification process. Data were analysed across the domains of endoscopic activity, waiting time targets, workforce, COVID-19, safety, GI bleeding, anaesthetic support, equipment and decontamination. Outcome variables from each section of the census were analysed against independent variables derived from service-specific core demographic data (JAG accreditation status, sector and region) using a variety of statistical methods. Results: Overall, 321 services completed the census, with information pertaining to 393 individual units (response rate 79.2%). In 2020, just over 1.5 million endoscopic procedures were performed across all services. In the first 3 months of 2021, 66% of services met urgent cancer waits, 38.7% met routine waits and 33.9% met surveillance waits ( Figure 1 ). Workforce redeployment was the predominant reason cited for not meeting targets. There were significant regional differences in the proportion of patients waiting 6 or more weeks (p = 0.001). During the pandemic, 64.8% of NHS services had staff redeployed and there was a mean sickness rate of 8.5% with no clear variation across sectors or regionally. Endoscopic activity was outsourced to the private sector in 21.6% of services. Services were, on average, at 79.3% activity compared to 2 years ago. JAG accredited services are more likely to meet urgent cancer waits, with a lower proportion of patients waiting 6 weeks or more (p = 0.03). Clinical endoscopists, who make up 11% of the endoscopist workforce, have a significantly greater number of annual planned sessions per individual than consultant colleagues, who make up 75% of the workforce. Over 10% of services stated that equipment shortage interferes with service delivery. Conclusions: Services are adapting to continued pressure and there are signs of a focussed response to demand during a time of ongoing uncertainty. These findings will inform ongoing guidance from JAG and relevant stakeholders.